STUDY OF SERUM MAGNESIUM, HBA1 C AND MICROALBUMINURIA IN DIABETIC RETINOPATHY - VAMSI KRISHNA CHITTIMOJU,; SUJATHA PASULA, (International Journal of Pharma and Bio Sciences, 2013)
Diabetic retinopathy is a sight threatening complication of diabetes mellitus and is one of the leading causes of acquired blindness. There is a series of risk factors related to the development and progression of diabetic retinopathy such as hypomagnesemia, dyslipidemia, duration of diabetes, poor diabetes control. There was a significant increase in the HbA1c and microalbumin were as magnesium is decreased in urine in diabetic patients with retinopathy and also in diabetic patients without retinopathy, when compared to the control group.The severity of diabetic retinopathy in the studied groups was influenced by factors such as duration of diabetes mellitus, good glycemic control, hypomagnesemia and microalbuminuria.